Agricultural Extension Systems: Institutional and Fiscal Perspectives in Nepal - Pandey, Santosh (Journey for Sustainable Development and Peace Journal, 2026)
This study critically explores the transformation of agricultural extension in post-federal Nepal on its institutional structure, intergovernmental budgetary allocation trends, and agricultural extension service delivery challenges across different government tiers through a systematic review of literature. The findings reveal that despite constitutional reconfiguration of extension responsibilities to different government tiers, the operational framework remains fragmented due to overlapping roles, ambiguous jurisdictional limits, and poor intergovernmental coordination. Although the constitution has undergone a transformation of centralized pre-federal institutional restructures by evolving new entities such as federal, provincial agricultural ministries, Agricultural Knowledge centers and municipal agricultural units, these functional aspects of these institutions often indicate limited technical capacities and weak linkages among research, extension and education aspects. The study concludes that agricultural extension urges a clear institutional role, equitable fiscal allocation among different government tiers, an effective intergovernmental coordination mechanism and a strategic shift towards a participatory, community-based, knowledge-driven extension model in order to align with the transformative potential of federalism.